Edukasi hukum digital dalam meningkatkan kesadaran pengguna terhadap serangan phishing di whatsapp - Wijaya, Alfan Nasrulloh (Maliki Interdisciplinary Journal, 2025)
The development of digital technology, especially the use of WhatsApp, brings many conveniences in daily communication, but also raises risks, such as increasingly rampant phishing attacks. One striking case is fraud through fake invitations on WhatsApp, which causes victims to lose personal data and suffer financial losses. This study aims to analyze the phenomenon of phishing on WhatsApp and propose a solution in the form of digital legal education to increase public awareness of the threat. This study uses a literature review method to formulate relevant solutions. Data were collected from the Electronic Information and Transactions Law (UU ITE) and related literature, and critically analyzed to obtain strategic steps to prevent phishing. The results of the study show that digital legal education that focuses on understanding the ITE Law, especially Articles 28 and 30, is expected to help the public understand the dangers of phishing and steps to prevent it. Strategies such as socialization of the ITE Law through digital platforms, webinars, collaboration with influencers, and strengthening digital literacy are predicted to be effective in increasing public awareness. Digital legal education can be an important solution in minimizing losses due to phishing, while also supporting the creation of a safe and protected digital ecosystem.